1999
DOI: 10.1053/ejvs.1998.0797
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Reflux and Venous Diameter Change in the Proximal Lower Limb Veins During a Standardised Valsalva Manoeuvre

Abstract: normal values for VDrest and VDmax as well as reflux time during a standardised Valsalva manouevre were assessed in the proximal lower limb veins. The influences of BMI, sex and family history were investigated. The described standardised Valsalva manoeuvre led to highly reproducible results and can be recommended for further research projects or as a routine procedure for the assessment of venous reflux.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
67
0
4

Year Published

2002
2002
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 7 publications
5
67
0
4
Order By: Relevance
“…We have studied all our patients with 2D ultrasound, color and spectral Doppler. Although, there are different methods described to elicit and measure the venous reflux, we used the Valsalva maneuver because of ease of performance [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…We have studied all our patients with 2D ultrasound, color and spectral Doppler. Although, there are different methods described to elicit and measure the venous reflux, we used the Valsalva maneuver because of ease of performance [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, chronic venous disease is strongly influenced by genetic variance. 24,25 This issue was also addressed in an elaborate genetic analysis of 68 large pedigrees that included 80 nuclear families. 26 The authors found an astoundingly strong genetic variance, namely penetrance frequencies between 70% and 92%.…”
Section: Discussionmentioning
confidence: 99%
“…Although, there are different methods described to elicit and measure the venous reflux, we used the Valsalva maneuver because of ease of performance. 6,7 In this study we had observed varicose veins more in male patients in compare to females (43 and 7). In contrast to us Callam MJ et al 2 and Evans CJ et al 9 described a higher prevalence of varicose veins in women in compare to man.…”
Section: Discussionmentioning
confidence: 49%